Relationship between soluble F11 receptor and ischemic heart disease in hemodialysis patients - Bakry, Seham; El-demery, Ahmed Bahgat (African Journal of Nephrology, 2010)
<p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background: Cardiovascular disease is a major cause ofmorbidity and mortality in hemodialysis patients, there isincreasing evidence that platelets are major contributorsto atherosclerosis, which is mediated through F11receptors. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Methods: Our study included 40 hemodialysis patientsdivided into two groups:Group 1: included 20 hemodialysis patients withischemic heart disease (IHD), Group 2: included 20hemodialysis patients without ischemic heart disease,they were compared with 20 age and sex matchedcontrols, soluble F11 receptor (sF11R) and highsensitivity C-reactive protein (hs-CRP) were measuredby enzyme-linked immunosorbent assay (ELISA). <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: sF11R was significantly higher in hemodialysispatients than controls; it showed significant differencebetween group 1, group 2 patients and controls. sF11Rshowed significant positive correlation with hs-CRP. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: sF11R can be considered a marker of IHDin hemodialysis patients.